A systematic review and meta-analysis of couple-based intervention on sexuality and the quality of life of cancer patients and their partners. - Li, Minjie; Chan, Carmen W. H.; Chow, Ka Ming; Xiao, Jinnan; Choi, Kai Chow (Supportive Care in Cancer, 2020)
Purpose: To synthesize the characteristics and effects of couple-based intervention on sexuality and the quality of life (QOL) of cancer patients and their intimate partners and its implications for future research and practice.Methods: A systematic review and meta-analysis of randomized and non-randomized controlled studies of interventions was conducted in nine English databases and two Chinese databases, with identification of related studies published in English and Chinese. The quality of the studies was assessed using the tools of the Effective Public Health Practice Project.Results: A total of 33 articles were identified for systematic review and 23 articles were identified for meta-analysis. For patients, the effect size was 0.42 (Hedges's g, 95% CI = 0.05-0.78, p = 0.03) for physical health. For partners, the effect size was 0.52 (Hedges's g, 95% CI = 0.06-0.98, p = 0.03) for sexual relationships. However, moderate to high heterogeneity was reported. Effects on sexual function, sexual self-concept, and mental health for couples were not significant.Conclusion: Couple-based interventions had small to medium-sized effects on physical health for cancer patients. Partners could derive medium effects for improvement in sexual relationships from couple-based intervention. Future research should pay more attention to sexual self-concept in cancer patients and target types of cancer that are more likely to compromise sexuality and QOL.Prospero Registration: The systematic review and meta-analysis has been registered in PROSPERO with registration number: CRD42019119047.